WHO HAS THE AUTHORITY TO DETERMINE THE TERM OF OFFICE FOR THE LEADERSHIP OF THE KPK (KOMISI PEMBERANTASAN KORUPSI)? - Nabilla, Shinta; Ahmad, Kamaruzzaman Bustamam; Makinara, Ihdi Karim (Universitas Islam Negeri Ar-Raniry, 2024)
The implementing of the Constitutional Court’s decisions may be direct or require the establishment of the implementating rules. Implementating rules is present when a test affects the cancellation of a rule that is contrary to the UUD. Generally, this follow-up is implemented with the emergence of a post-revised law by its creator. But it will take a long time, and need for legal certainty cannot wait until the investigation is completed. In this interest the product of the law was born answering the problem. Then what if the legal product intended to replace the law does not actually have the urgency of interest as required to provide legal certainty. This reseacrh examines the urgency of Keppers in enforcing Constitutional Court Decision No. 112/PUU-XX/2022 on the age limit and term of office of the KPK chairman given that there are other legal products that can enforce the judgment. This research is normative legal research. The results of the research show that the presence of Keppres does not contain urgency until a study or improvement of the KPK Act by the DPR is carried out. Even if it is of urgent value, Perppu can be an alternative given that Perppu is in line with the law and is regulatory while Keppres is only a settlement. This article consists of four sections starting with the introduction, the explanation, and the conclusion.